Vocabulary Learning Strategies Used by the High- Proficiency Learners - Tania Tahmina (Hasanuddin University, 2023)
Vocabulary learning strategies played a significant role in EFL learners’ vocabulary acquisition. All language learners use their own chosen vocabulary learning strategies; however, appropriateness in selecting strategies can lead them to success. The objectives of the study were to explore the vocabulary learning strategies used by high-proficiency language learners of the Department of English at Jagannath University, Bangladesh, and to describe the reasons behind choosing these strategies. A mixed-methods approach was used. Thirteen high achiever undergraduate students of the Department of English, Jagannath University, Bangladesh, participated in this research. An adaptation of Schmitt’s (1997) questionnaire, learners’ scores, and interviews were used as instruments to collect data. The result showed that the Cognitive (Consolidation) Strategy Category no. 25: “I repeat the word to myself” was the high achievers’ most frequently used strategy. The next preferred strategies were Determination (Discovery) Strategies Category no. 4: “I guess the meaning from the context” and Category no. 5: “I use an English-Bangla dictionary.” The Memory (Condensation) Strategy Category no. 17: “I connect the word to a personal experience”, Cognitive (Condensation) Strategy Category no. 29: “I take notes about the new words”, and Determination (Discovery) Strategy Category no. 6: “I use an English dictionary” were in the third position. These strategies ensured their spontaneous learning and aided them in becoming autonomous learners. The findings of this study will contribute to learners, teachers, and researchers.